2022
DOI: 10.1007/s00701-022-05215-9
|View full text |Cite
|
Sign up to set email alerts
|

Open-aqueduct LOVA, LIAS, iNPH: a comparative clinical-radiological study exploring the “grey zone” between different forms of chronic adulthood hydrocephalus

Abstract: Purpose The definition of chronic adult hydrocephalus encompasses different pathological entities with overlapping characteristics, including long-standing overt ventriculomegaly in adults (LOVA), late-onset idiopathic aqueductal stenosis (LIAS) and idiopathic normal pressure hydrocephalus (iNPH). The aim of our study was to identify preoperative clinical and radiological features peculiar of these diseases providing some pathophysiology inferences on these forms of hydrocephalus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Characteristic neuroimaging finds of LOVA include (third and lateral) ventriculomegaly, decreased prominence of cortical sulci, macrocephaly, and expansion of the sella turcica due to compensatory mechanisms ( 156 ). In cases where LOVA occurs with an open aqueduct, where it may be differentiated from Late Onset Idiopathic Aqueductal Stenosis (LIAS), it becomes more crucial to distinguish it from NPH due to their clinical and symptomatic overlap ( 157 ). ICP monitoring in LOVA patients was shown to correlate with patient conditions pre- and post-surgery ( 158 ), and CSF dynamics was recommended to differentiate them from NPH patients ( 159 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic neuroimaging finds of LOVA include (third and lateral) ventriculomegaly, decreased prominence of cortical sulci, macrocephaly, and expansion of the sella turcica due to compensatory mechanisms ( 156 ). In cases where LOVA occurs with an open aqueduct, where it may be differentiated from Late Onset Idiopathic Aqueductal Stenosis (LIAS), it becomes more crucial to distinguish it from NPH due to their clinical and symptomatic overlap ( 157 ). ICP monitoring in LOVA patients was shown to correlate with patient conditions pre- and post-surgery ( 158 ), and CSF dynamics was recommended to differentiate them from NPH patients ( 159 ).…”
Section: Discussionmentioning
confidence: 99%
“…ICP monitoring in LOVA patients was shown to correlate with patient conditions pre- and post-surgery ( 158 ), and CSF dynamics was recommended to differentiate them from NPH patients ( 159 ). A noninvasive and accurate diagnostic score consisting of clinical features like age, presence/absence of the Hakim triad, headache, nausea/vomit, and neuroradiological features (evaluated on MRI) like the head circumference, EI-x, 3 V width, DESH, sellar bone distortion with the bulging of the 3 V floor was proposed recently by Palandri et al ( 157 ) which was shown to classify probable NPH patients from LOVA and LIAS patients with a high AUC of 0.97, sensitivity of 95.1%, and specificity of 90.6%. Higher values of this diagnostic score correlates with higher EI-x, 3 V width, head circumference, 3 V floor bulging, and lower prominence of DESH which incorporates distinctive neuroradiological findings in LOVA as opposed to NPH.…”
Section: Discussionmentioning
confidence: 99%